2017
DOI: 10.3233/jad-161023
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort

Abstract: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…We found that BPSD, and especially agitation, aberrant motor behavior, and sleep disturbance, was improved through treatment in the wards for patients with dementia. These findings are consistent with previous studies showing that treatment of older person with dementia at hospital improved BPSD, especially agitation (Bellelli et al, 1998; Colombo et al, 2007; Kitamura et al, 2013; Rouch et al, 2017; Sugiyama et al, 2013; Taniguchi et al, 2013). These results indicate that the treatment at hospital is effective in improvement of BPSD, especially agitation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that BPSD, and especially agitation, aberrant motor behavior, and sleep disturbance, was improved through treatment in the wards for patients with dementia. These findings are consistent with previous studies showing that treatment of older person with dementia at hospital improved BPSD, especially agitation (Bellelli et al, 1998; Colombo et al, 2007; Kitamura et al, 2013; Rouch et al, 2017; Sugiyama et al, 2013; Taniguchi et al, 2013). These results indicate that the treatment at hospital is effective in improvement of BPSD, especially agitation.…”
Section: Discussionsupporting
confidence: 93%
“…The sample size was relatively small and the information on caregivers was limited, especially for the family caregiver burden. Although the rate of re-hospitalized was relatively high in the previous study (Rouch et al, 2017), we did not investigate after discharge. Therefore, the results have to be interpreted with caution and a further study focused on the caregiver burden is needed.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…DAD, NPI, CDR, and MMSE have been used to evaluate ADL, BPSD, and cognitive function in various dementias, as well as in diseases that cause dementia symptoms, whereas DLB and FTLD are disease-specific evalu-ation scales. DAD, NPI, CDR, and MMSE are utilized frequently [20][21][22].…”
Section: Discussionmentioning
confidence: 99%